The Photophysiological Response of Nitrogen-Limited Phytoplankton to Episodic Nitrogen Supply Associated With Tropical Instability Waves in the Equatorial Atlantic - Sherman, Jonathan; Subramaniam, Ajit; Gorbunov, Maxim Y.; Fernández-Carrera, Ana; Kiko, Rainer; Brandt, Peter; Falkowski, Paul G. (Frontiers in Marine Science, 2022)
In the Equatorial Atlantic nitrogen availability is assumed to control phytoplankton dynamics. However, in situ measurements of phytoplankton physiology and productivity are surprisingly sparse in comparison with the North Atlantic. In addition to the formation of the Equatorial cold tongue in the boreal summer, tropical instability waves (TIWs) and related short-term processes may locally cause episodic events of enhanced nutrient supply to the euphotic layer. Here, we assess changes in phytoplankton photophysiology in response to such episodic events as well as short-term nutrient addition experiments using a pair of custom-built fluorometers that measure chlorophyll a (Chl a) variable fluorescence and fluorescence lifetimes. The fluorometers were deployed during a transatlantic cruise along the Equator in the fall of 2019. We hypothesized that the Equatorial Atlantic is nitrogen-limited, with an increasing degree of limitation to the west where the cold tongue is not prominent, and that infrequent nitrate injection by TIW related processes are the primary source alleviating this limitation. We further hypothesized phytoplankton are well acclimated to the low levels of nitrogen, and once nitrogen is supplied, they can rapidly utilize it to stimulate growth and productivity. Across three TIW events encountered, we observed increased productivity and chlorophyll a concentration concurrent with a decreased photochemical conversion efficiency and overall photophysiological competency. Moreover, the observed decrease in photosynthetic turnover rates toward the western section suggested a 70% decrease in growth rates compared to their maximum values under nutrient-replete conditions. This decrease aligned with the increased growth rates observed following 24 h incubation with added nitrate in the western section. These results support our hypotheses that nitrogen is the limiting factor in the region and that phytoplankton are in a state of balanced growth, waiting to “body surf” waves of nutrients which fuel growth and productivity.